Antioxidant Status, Lipid Metabolism, Egg Fatty Acids, and Nutritional Index of White-Egg Laying Hens Fed Flaxseed Cake - Youssef A. Attia; Ahmed A. Al sagan; El-sayed O. S. Hussein; Marai J. Olal; Tarek A. Ebeid; Rashed A. Alhotan; Mohammed M. Qaid; Fulvia Bovera; Heba A. Shehta; Vincenzo Tufarelli (The Journal of Poultry Science, 2024)
Flaxseed cake contains high levels of phenolic compounds, which have numerous biological activities, as well as a considerable amount of omega-3 fatty acids, such as α-linolenic acid, which remains after oil extraction. In this study, we examined the effects of flaxseed cake meal (FSCM) on the antioxidative status, lipid metabolism, egg fatty acid profile, and egg health index of white-egg laying hens. A total of 63 Hisex White laying hens were divided into three experimental treatment groups and fed diets containing 0, 5, or 10% FSCM from 48 to 58 weeks of age. Feeding with 5 and 10% FSCM did not significantly (p>0.05) influence total lipid, triglyceride, total cholesterol, very low-density lipoprotein-cholesterol, or low-density lipoprotein-cholesterol concentrations, or the high-/low-density lipoprotein ratio in the serum and egg yolk; however, 10% FSCM significantly (P<0.05) increased serum high-density lipoprotein. Dietary FSCM also did not affect (P>0.05) antioxidant markers in the eggs and blood plasma. Notably, dietary inclusion of FSCM significantly increased (P<0.05) total n-3 polyunsaturated fatty acids (PUFAs), α-linolenic acid, docosahexaenoic acid, and eicosapentaenoic acid levels in egg yolk, whereas the n-6:n-3 PUFAs ratio was markedly (P<0.05) decreased in a dose-dependent manner. Moreover, including 5–10% FSCM improved (P<0.05) egg health indices, with 10% being the most beneficial. Together, these findings indicated that the inclusion of up to 10% FSCM in laying hen diets improved egg yolk lipid and fatty acid profiles, as well as egg quality and nutritional and metabolic indices.